Questioning the utility of round spermatid injections in men with non‐obstructive azoospermia. (13th April 2021) - Barda, Shimi; Mano, Roy; Lehavi, Ofer; Kleiman, Sandra E.; Yossepowitch, Ofer; Azem, Foad; Hauser, Ron; Dekalo, Snir
Abstract: Background: Data on who among the infertile male population may benefit from round spermatid injections (ROSI) are lacking. Objective: To determine the probability of finding round spermatids suitable for ROSI in men with non‐obstructive azoospermia (NOA) in whom no spermatozoa were retrieved at testicular sperm extraction. Materials and methods: Four‐hundred fifty‐seven consecutive men with azoospermia underwent testicular sperm extraction. Clinical examination included age, secondary sexual characteristics, testicular size, reproductive hormone estimation, karyotyping, and Y chromosome microdeletion analyses. Histologic examination was performed, and histologic classification was determined by the most advanced spermatogenetic cell identified in the combined histologic and cytologic examination. Results: Of the 457 azoospermic men, 342 were diagnosed with NOA, and 148 (148/342, 43%) had mixed atrophy on histopathology and retrievable spermatozoa. No spermatozoa were found in 194/342 men with NOA (57%). Histopathology diagnosed 145/194 (75%) of them with Sertoli cell only, 45/194 (23%) with spermatocyte maturation arrest, and 4/194 (2%) with spermatid maturation arrest. Conclusions: Histopathologically identified round spermatids without spermatozoa were rare in men with NOA. Only very few of them are likely to reap the benefits of ROSI, thus presenting the need to reconsider its actual clinical value.